2022
DOI: 10.1371/journal.pone.0267049
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and differentiation of tobacco-derived and synthetic nicotine products: Addressing an urgent regulatory issue

Abstract: There is significant regulatory and economic need to distinguish analytically between tobacco-derived nicotine (TDN) and synthetic nicotine (SyN) in commercial products. Currently, commercial e-liquid and oral pouch products are available that contain tobacco-free nicotine, which could be either extracted from tobacco or synthesized. While tobacco products that contain TDN are regulated by FDA Center for Tobacco Products, those with SyN are currently not in the domain of any regulatory authority. This regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 16 publications
0
33
0
Order By: Relevance
“…Conversely, a higher percentage of adult users reported using unflavored and tobacco-flavored e-cigarette devices relative to users in younger age categories. These data along with other recent studies [ 15 , 17 ] strongly indicate that selective policy action is unlikely to effectively address the problem of adolescent e-cigarette use, particularly as tobacco companies continue to develop new products and marketing tactics to maintain profits and circumvent regulations [ 38 , 39 ]. Given the limited effectiveness of e-cigarettes as adult smoking-cessation devices [ 40 , 41 ] and the role of flavors in promoting adolescent e-cigarette use [ 6 , 30 , 34 ], the FDA should adopt more comprehensive policies that prohibit all flavors, including menthol, in all types of e-cigarette devices to help achieve its stated goal of stopping the public health crisis of adolescent e-cigarette use [ 12 ].…”
Section: Discussionmentioning
confidence: 94%
“…Conversely, a higher percentage of adult users reported using unflavored and tobacco-flavored e-cigarette devices relative to users in younger age categories. These data along with other recent studies [ 15 , 17 ] strongly indicate that selective policy action is unlikely to effectively address the problem of adolescent e-cigarette use, particularly as tobacco companies continue to develop new products and marketing tactics to maintain profits and circumvent regulations [ 38 , 39 ]. Given the limited effectiveness of e-cigarettes as adult smoking-cessation devices [ 40 , 41 ] and the role of flavors in promoting adolescent e-cigarette use [ 6 , 30 , 34 ], the FDA should adopt more comprehensive policies that prohibit all flavors, including menthol, in all types of e-cigarette devices to help achieve its stated goal of stopping the public health crisis of adolescent e-cigarette use [ 12 ].…”
Section: Discussionmentioning
confidence: 94%
“…A total of 362 records were removed at this stage and the full texts of the remaining 27 articles were scanned. Accordingly, a total of 23 articles were included in the review. ,− ,, Figure shows the PRISMA diagram that summarizes the steps of the selection process.…”
Section: Resultsmentioning
confidence: 99%
“…However, if synthetic nicotine was purified to become 99% ( S )-nicotine, TFN becomes indistinguishable from TDN if the previously described analytical methods were used. Other analytical methods were found to be used for this purpose . In fact, it was suggested that TFN and TDN could be distinguished by detecting specific impurities like tobacco-specific nitrosamines, nicotine degradants, and metals in TDN samples from one hand and synthetic precursors and residual solvent impurities in TFN samples from the other .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Today there exist a number of analytical challenges for the tobacco industry and nicotine testing communities (54)(55)(56)(57)(58).…”
Section: A Perspectivementioning
confidence: 99%